Dynamic Responses to Policy and Exogenous Shocks in an Empirical Developing-Country Model with Rational Expectations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
The dynamic responses of a developing economy to a variety of policy and external shocks are studied using an empirical macroeconomic model which embodies rational expectations, perfect capital mobility, and import rationing. These features, which are relatively new in developing-country modelling, prove to be quite important in determining the model's dynamic properties. This suggests that macroeconomic management in developing countries--such as that involved in short-run stabilization--requires that such features be explicitly taken into account.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet